A forage training guide for trainers: Grass 2 Cash @Scale Project - Kagendo, Sophia; Jeptoo, Mercy; Valeton, Alexander; Odhiambo, Ruth A.; Muthomi, Fredrick K.; Misoi, Solomon K.; Mugo, Peggy K.; Sibiko, Kenneth W.; Hansen, Andreas; Ohmstedt, Uwe; Mwendia, Solomon W.; Notenbaert, An M.O.; et al. (2023)
This trainer's guide provides comprehensive notes for anyone offering training on forage production and utilization. Topics covered include the rationale for forage production (with potential business models), the entire production process from land preparation, forage establishment, management, harvesting, to conservation. It also provides guidelines on proper livestock feeding to achieve optimal production potential. The trainer’s guide is meant to accompany the “Multimedia Forage Farmer Training Modules”. Information is presented in a multimedia format, with pictorial illustrations and links to informative Shamba Shapeup YouTube videos. Furthermore, the guide is well-structured, with clear learning objectives and quizzes for the trainer to assess the farmers’ level of understanding. This resource is valuable for training facilitators, agricultural extension providers, agriculture students, and researchers.